Biological strategies for detoxification of Hexavalent chromium - RACHNA BHATERIA; RENU DHAKA (International Journal of Pharma and Bio Sciences, 2017)
Hexavalent Chromium is mobile, highly toxic, carcinogenic and mutagenic. It is released into the environment from various industrial processes. In contrast trivalent chromium is less toxic and immobile. Hence, Cr (VI) can be detoxified by converting it to Cr (III). Reduction of Cr (VI) can be achieved by chemical or biological means. Conventional methods for removing metals from contaminated sites include chemical precipitation, oxidation/reduction, ion exchange, filtration, use of membranes, evaporation and adsorption on activated coal, alum, kaolinite and ash. The biological treatment of hexavalent chromium [Cr (VI)] has fascinated people because this alternative is more efficient and less expensive than conventional physicochemical treatments. Microbial reduction of hexavalent chromium has practical importance because biological strategies are part of green technology that is cost effective and eco friendly. The problem of detoxification of chromium can be overcome by bioremediation process which uses plants like hyperaccumulators and different types of microbes for the treatment of contaminants. It helps in complete restoration of the contaminated site. This review focuses on the bioremediation of chromium by plants and microbes like bacteria, fungus, yeast, algae and genetically modified crops.